Healthcare Meets AI: Innovations, Applications, and Ethical Considerations - Khan, Murad; Sherani, Abdul Mannan Khan (BULLET : Jurnal Multidisiplin Ilmu, 2024)
AI is transforming healthcare through enhancing diagnostic capability, treatment planning, and drug discovery or even in the management of care organizations. AI technologies are used for differential diagnostics, individual management of patients, increasing the effectiveness of treatment in different branches of medicine and optimizing the work of health care systems. The use of machines in diagnostics, risks and outcomes forecast, and treatments like individualized cancer therapies, are already being seen to provide realistic value and enhance the quality of patients’ lives and yield as well as the pace of scientific discovery faster. The author believes that similar to creating new drugs, applying Artificial Intelligence in drug discovery process and other Healthcare aspects shows how beneficial it can be. Nevertheless, people can use AI extensively in healthcare practices, appearing to come up with certain ethical concerns. These are among the emerging issues: safe and secure data and, in particular, avoiding the risks of bias within artificial intelligence models, and respondent to transparency of decisions made by artificial intelligence. To reduce the unfair treatment of certain populations AI systems should be trained on diverse data and the data used to make decisions should be understandable. However, questions arising from patient self-determination, and especially informed consent can also be a challenge to such innovations in this regard hence the need to handle with care. This review aims at reviewing current AI advances and health care, review the ethical issues arising from these gadgets and lastly the importance of a responsible use. The things to do to augment its possibilities and avoid potential risks will entail retaining patient sovereignty; governing the impact of AI systems to be fair; and deem AI accountability. With involvement of stakeholders from the healthcare, informational technology, and the government, AI has the potential to revolutionize health care service delivery for improved efficiency and social justice.